2020
DOI: 10.1128/jvi.01572-19
|View full text |Cite
|
Sign up to set email alerts
|

PARP1 Enhances Influenza A Virus Propagation by Facilitating Degradation of Host Type I Interferon Receptor

Abstract: Influenza A virus (IAV) utilizes multiple strategies to confront or evade host type I interferon (IFN)-mediated antiviral responses in order to enhance its own propagation within the host. One such strategy is to induce the degradation of type I IFN receptor 1 (IFNAR1) by utilizing viral hemagglutinin (HA). However, the molecular mechanism behind this process is poorly understood. Here, we report that a cellular protein, poly(ADP-ribose) polymerase 1 (PARP1), plays a critical role in mediating IAV HA-induced d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 54 publications
0
37
0
1
Order By: Relevance
“…Several previous studies have demonstrated that PARP1 is critical for viral replication [35,42,43]. For example, PARP1 has been reported to interact with hemagglutinin (HA) of influenza A virus (IAV) and promote its replication by triggering the degradation of host type I IFN receptor [44]. In addition, the ADP-ribosylation of adenoviral core proteins displays an antiviral defense mechanism [34].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have demonstrated that PARP1 is critical for viral replication [35,42,43]. For example, PARP1 has been reported to interact with hemagglutinin (HA) of influenza A virus (IAV) and promote its replication by triggering the degradation of host type I IFN receptor [44]. In addition, the ADP-ribosylation of adenoviral core proteins displays an antiviral defense mechanism [34].…”
Section: Discussionmentioning
confidence: 99%
“…Viruses can employ a variety of mechanisms to suppress the host innate immune system, [33][34][35] thus evading from crucial antiviral responses, like the IFN signaling pathways, to facilitate virus propagation and dissemination. Here, our study demonstrated that SARS-CoV-2 infection induced attenuated pro-inflammatory cytokines/chemokines and IFN responses in both Calu3 and Caco2 cells, despite robust virus infection and propagation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, HA protein was shown to trigger ubiquitination of IFNAR to attenuate the type I IFN signaling pathway [162]. The follow-up work showed that poly (ADP-ribose) polymerase 1 (PARP1) functions as an interacting partner of HA protein to mediate the HA-induced IFNAR degradation [163]. NS1 is the most important IFNs antagonist protein via mechanisms including inhibition of the TRIM25-mediated RIG-I ubiquitination, suppression of protein kinase R (PKR), phosphorylation of IκB kinases (IKK) α and β in the NF-κB pathway, interruption of the phosphorylation of STAT1, STAT2, and STAT3 [39,115], and degradation of OTUB1 [138].…”
Section: Of 23mentioning
confidence: 99%